2018
DOI: 10.1007/s10926-018-9782-x
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Capacity Evaluation in Different Societal Contexts: Results of a Multicountry Study

Abstract: Purpose To examine factors associated with Functional Capacity Evaluation (FCE) results in patients with painful musculoskeletal conditions, with focus on social factors across multiple countries. Methods International cross-sectional study was performed within care as usual. Simple and multiple multilevel linear regression analyses which considered measurement's dependency within clinicians and country were conducted: FCE characteristics and biopsychosocial variables from patients and clinicians as independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…For example, Gross and Battié ( 2005 ) found that “younger, male subjects who reported lower levels of perceived disability and pain intensity lifted at higher levels”. The last three criteria were confirmed in a multicountry study (Ansuategui Echeita et al 2019 ).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…For example, Gross and Battié ( 2005 ) found that “younger, male subjects who reported lower levels of perceived disability and pain intensity lifted at higher levels”. The last three criteria were confirmed in a multicountry study (Ansuategui Echeita et al 2019 ).…”
Section: Introductionmentioning
confidence: 73%
“…Due to a large number of days on sick leave, rehabilitation measures and pension applications that are related to musculoskeletal disorders (MSD) (Bevan 2015 ; Murray et al 2015 ; Deutsche Rentenversicherung Bund (DRV) 2019a ), the question of whether an individual's physical capacity meets the physical demands of work frequently arises in the context of occupational and rehabilitation medicine. To promote a valid assessment of the ability to safely perform activities required at work, Functional Capacity Evaluation (FCE) procedures became part of common clinical practice (Ansuategui Echeita et al 2019 ). These assessments are defined as “an evaluation of capacity of activities that is used to make recommendations for participation in work while considering the person’s body functions and structures, environmental factors, personal factors and health status” (Soer et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…If a patient has reached MMI, but has failed to achieve their pre-injury or prior level of work status, then a physician can utilize a functional capacity evaluation to determine the patient’s ability and impose final work restrictions[ 69 ]. Although the results of the FCE are often used to set work limitations, some studies have questioned its utility as FCE does not take biopsychosocial factors into account and possibly measures a patient’s tolerance to an activity as opposed to the patient’s true ability[ 69 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…For research question 1, cross-sectional analyses with baseline data were performed. First, Spearman partial correlation analyses were performed, corrected for sex and age due to known differences in lifting capacity, HRV and QST [ 47 , 57 , 58 ]. Second, multiple regression analyses were performed, with each functioning measurement separately as dependent variable, one variable representative of each CS indicator as fixed independent variables, and participants’ characteristics as potential confounders (including the correction for age and sex).…”
Section: Methodsmentioning
confidence: 99%